2010
DOI: 10.1038/onc.2010.243
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GLI, but not Smoothened, induces apoptosis in chronic lymphocytic leukemia cells

Abstract: The Hedgehog (Hh) pathway regulates cell proliferation and survival and contributes to tumorigenesis. We investigated the expression and function of this pathway in B-cell chronic lymphocytic leukemia (CLL) cells and in healthy B lymphocytes. Profiling of cognate Hh pathway members revealed reduced expression of two key Hh signaling effectors, Smoothened (SMOH) and GLI, in CLL cells, whereas transcription levels of other investigated members resembled normal B-lymphocyte levels. Examining the functional role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 63 publications
4
70
0
Order By: Relevance
“…96 In contrast, Desch et al found that key participants of the Hh signaling cascade (including SMO and GLI1) were not differentially expressed in B-CLL cells over normal B cells. 97 In addition, in their studies, SMO inhibition alone did not influence B-CLL cell survival in vitro. However, GANT61 (a direct Gli1 inhibitor) caused significant apoptosis in B-CLL cells but not normal B cells in vitro, which could be rescued by stromal coculture but not recombinant SHH ligand alone.…”
Section: Lymphoma and Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…96 In contrast, Desch et al found that key participants of the Hh signaling cascade (including SMO and GLI1) were not differentially expressed in B-CLL cells over normal B cells. 97 In addition, in their studies, SMO inhibition alone did not influence B-CLL cell survival in vitro. However, GANT61 (a direct Gli1 inhibitor) caused significant apoptosis in B-CLL cells but not normal B cells in vitro, which could be rescued by stromal coculture but not recombinant SHH ligand alone.…”
Section: Lymphoma and Cllmentioning
confidence: 99%
“…This suggests that other signaling pathways converging on GLI1 expression were responsible. 97 Decker et al recently demonstrated that both Hh mediator expression and SMO inhibitor responsiveness were variable in different patients. They found that 60% of their CLL cohort responded to SMO inhibition.…”
Section: Lymphoma and Cllmentioning
confidence: 99%
“…In addition to Smo antagonists, other inhibitors were used to block Hh signaling like the small molecule inhibitor of GLI1 and GLI2 transcription factors, GANT61, which induced colon carcinoma cell death in a higher extent respect to the conventional Smo inhibitor cyclopamin [74] . The treatment with GANT61 reduced also the expression of the target gene Patched and decreased the viability of chronic lymphocytic leukemia cells [75] . Recently, the systemic antifungal itraconazole which failed to bind to Smo at the same binding site of cyclopamine, showed a potent antagonism for the Hh signaling pathway associated with anti-tumor activity in a mouse medulloblastoma allograft model [76] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…37 In our previous work, we could show that HH pathway inhibition by SMO inhibitors could block the expansion of murine lymphomas in vitro and in vivo. 16 In addition, human lymphoid malignancies, such as diffuse large B-cell lymphoma, 38 NPM-ALK-driven anaplastic large cell lymphoma, 39 mantle cell lymphoma, 40 43 Therefore, the aim of the present study was to identify biomarkers and clinical parameters, which can discriminate in between SMO-inhibitor responsive and resistant CLLs and to identify mechanisms of HH pathway activation in CLL. …”
mentioning
confidence: 99%